Topographic changes in macula and its association with visual outcomes in idiopathic epiretinal membrane surgery - Seung Min Lee; Sung Who Park; Iksoo Byon (PLoS ONE, 2025)
Purpose We investigated changes in macular topography and their association with visual acuity and metamorphopsia in the idiopathic epiretinal membrane (iERM). Methods Twenty-four eyes that underwent vitrectomy and ERM removal with internal limiting membrane peeling were included in this study. Best-corrected visual acuity (BCVA) and horizontal/vertical metamorphopsia scores (h and vM-scores in the M-chart) were assessed. The distances of fovea-disc (FD) and fovea-vascular arcade (FV), central subfield macular thickness (CSMT), and foveal location were measured using fundus photography, optical coherence tomography (OCT), and OCT angiography, respectively. Results The BCVA (logMAR) and vM-scores (P < 0.001, P = 0.014, respectively) improved after surgery. The distance of the FD decreased (P < 0.001) and FVs increased (P < 0.001, both). The fovea moved horizontally toward the disc (P < 0.001). The change in median total FVs (7.114 mm to 7.369 mm, P = 0.001) correlated with the change in BCVA (P = 0.049, Pearson’s [r] = -0.404). No topographic parameters were associated with an improvement in the vM score. Conclusions The macular topography significantly changed after iERM removal; the fovea moved nasally, and the distance between the superior and inferior vascular arcades increased. Such a change was relevant to the improvement in BCVA, but not metamorphopsia.